Practical and architectural aspects of sorting and searching - Nash, Nicholas C.A. (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2010)
The work in this dissertation was motivated by a desire to understand as well as to improve the performance of certain algorithms and data structures in practice. The performance of algorithms in practice is influenced by many interacting factors, of which one of the most important is the architecture of the machine where the algorithm or data structure is used. In this dissertation we consider architectural as well as other practical factors influencing the performance of sorting algorithms and data structures.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin.